An Approach to Artificial Intelligence as a Criminogenic Factor - Navarro-Dolmestch, Roberto Andrés (2025)
This paper examines the potential of artificial intelligence (AI) technologies to function as a criminogenic factor, namely as causes of criminal phenomena. The analysis distinguishes two perspectives from which this role may materialize. From a microcriminogenic perspective, it is argued that AI possesses the technical capacity to become directly or indirectly involved in criminal offenses or in conduct that, due to its dangerousness or harmfulness, should be criminalized. From a macrocriminogenic or structural standpoint, it is posited that AI-driven capitalism may increase social conflict or lead to an intensified reliance on the criminal justice system to protect the economic order built around AI.